Biomedical Engineering meeting - ., Sociedad Mexicana de Ingeneiria Biomedic (Revista Mexicana de Ingenieria Biomedica, 2018)
Many times, in discussions with students and biomedical engineers, emphasis has been placed on the lack of dissemination that our career still has, the lack of information that students have about the work of their area of study, the partial response of some sectors professionals facing the academic training and the activities of the biomedical engineer and, finally, the lack of integration that exists between the same biomedical engineers as a group.